Tutorial Tasmi’ Berbasis Computer Assisted Instruction (CAI) Pada Pembelajaran Maharah Istima’ - wijayanti wijayanti wijayanti (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2018)
Maharah istima 'in learning Arabic has a very important role for learners of foreign languages. From maharah istima ’one can get vocabulary, string words correctly so that they can finally convey ideas using the correct language. Therefore a foreign language learner who does not practice much listening will not be able to learn the language well. Maharah istima 'is a basic competency that must be mastered by learners of Arabic, so if a teacher is able to develop these competencies well then he has succeeded in learning Arabic so that it has an impact on the success of students in mastering Arabic properly. Computer Assisted Instruction (CAI) learning is one of the learning methods that uses educational software that is accessed through a computer where students can interact with it independently. This learning can convey the contents of the lesson, provide training, test the learning progress of students, stimulate the thinking of students to be more active, creative, and fun through educational software that has been accessed on a computer. And through this CAI-based tutorial learning can guide students thoroughly mastering istima's masterpiece material quickly and interestingly. Keywords : Tutorial, Tasmi’, Maharah Istima’, Computer Assisted Intruction